Catalan Secessionism within the Context of International Law - Pérez Unceta, José Antonio (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2015)
International Law is not conclusive regarding the mapping of the legal right of non-colonial people to self-determination, since the related estimate included in Resolution 2625 (XXV) of 1970 of the UN General Assembly is highly scarce, it has had an inconsistently highly politicized subsequent use within the frame of this organization and has been replaced in regional systems by non-discrimination and protection of such national minorities human right. However, the so-called safeguard term continues to apply and has been used in recent cases in international practice and counts on the support of one side of doctrine that believes in self-determination from an external point of view, including secession as the last measure in case of discrimination of national minorities and of serious massive systematic infringement of its human rights by the state they belong to. Two different legal requirements apply in the secessionism predicted by the Government of Catalonia. First of all, the right to self- determination of people as stated in International Law, particularly in the UN General Assembly, and, facing the problems its put into practice for this particular purpose arises, since there is neither discrimination nor oppression here. Secondly, the principle of democracy, separately considered as the mere will of its people’s members, not taking into consideration the rest of the requirements and circumstances that make part of the idea of democracy, such as respect to the law and to legal resolutions. In practice problems do not relate to the act passed on 9 November 2014, which has not met the requirements of the referendums called or supervised by international organizations and could eventually lead to a unilateral declaration of Independence.
Keywords: International Public Law; self-determination of people; national minorities; secession; Catalonia.